The photographer's guide to Luminar 4 - Carlson, Jeff (Rocky Nook, 2020)
Skylum's Luminar 4 is a great solution for both professional and amateur photographers who want to quickly create stunning photos. Luminar's advanced AI-based tools eliminate hours of traditional editing tasks, whether you're applying automatic tone and color adjustments, replacing dreary skies with more dynamic ones, or retouching portraits to smooth skin, remove blemishes, and accentuate flattering facial features. For those who want to dig into editing, powerful tools give you full control over your RAW and JPEG images, including advanced features such as layers, masks, blend modes, and lens correction. Luminar also works as a plug-in for other applications, such as Adobe Photoshop, Lightroom Classic, and Apple Photos, allowing round-trip editing and seamless integration with workflows you may already have in place. Luminar 4 is deceptively deep, and in The Photographer's Guide to Luminar 4, photographer Jeff Carlson helps you discover Luminar 4's best features to take full advantage of the program for all your photography needs. From importing your images to editing, managing, and exporting your files, Jeff showcases the power, precision, and control of Luminar while teaching you to work quickly and efficiently. In this book, he walks you through real-world landscape and portrait edits, and covers every tool and feature with the goal of helping you understand how to make Luminar improve your images. In this book you'll learn all about: " AI editing: Luminar 4's many AI-based tools eliminate hours of traditional editing tasks. Improve overall tone and color using just one slider, and enhance a sky using another without building masks or layers. Realistically replace the entire sky in one step, even when objects like buildings or trees intrude. Luminar identifies faces in photos, allowing you to smooth skin, sharpen eyes, brighten faces, and perform other portrait retouching tasks in minutes." Expert editing: Take advantage of Luminar's many professional tools to bring out the best versions of your photos. Enhance the look using tone controls and curves, dodging and burning, and tools built for specific types of images, such as Landscape Enhancer, Adjustable Gradient, and B & W Conversion. The Erase and Clone & Stamp tools make it easy to remove unexpected objects and glitches such as lens dust spots. Luminar's RAW editing engine includes real-time noise reduction and advanced color processing and sharpening tools, all completely non-des ...